Establishment and replacement of failures in Prosopis alba plantations in Santiago del Estero, Argentina - García, Jorge (2022)
The cost of implantation of a forest species not only contemplates the plantation activity itself, but also that of its subsequent replacement of failures. The objective of this study was to describe and determine the performance of the control tasks of picking and replacement of failures in plantations of Prosopis alba (white carob tree) under the influence of edaphic factors such as pH and electrical conductivity. The research focused on the framework of the Santiagueño Forest Program (PFS), Argentina, executed during the 2017–2018 afforestation campaign. The sample consisted of 3 producers with plots located in the Robles department of the Santiago del Estero province. The field work allowed to record the tasks of control of uprooting and replacement of failures and in turn, to evaluate the establishment of the plants under different edaphic factors. The study reflects an average plant loss percentage of 17% and shows that the replacement of 75 carob plants requires 0.12 wages (0.96 h). There is a strong correlation between the variables CE (ds / m) and plant mortality, in this sense a statistical model was obtained capable of estimating plant mortality based on the EC of the soil.